Healthcare Transformation In Saudi Arabia: Advancing Health Systems Through Practitioner-Centred Reform Under Vision 2030 (The Review of Diabetic Studies, 2024)
Saudi Arabia’s Vision 2030 has initiated one of the most integrated healthcare transformations in the region, aiming to enhance population health, improve service quality, and ensure ongoing system sustainability. Fundamental to this reform is the healthcare workforce, whose roles have expanded more than conventional clinical functions to encompass leadership, digital innovation, preventive care, and system governance. This overview considers the organisational transformation of the Saudi healthcare system under Vision 2030, with particular emphasis on the Health Sector Transformation Program and the Modern Healthcare Model. It critically analyses the developing responsibilities of healthcare practitioners and their contribution to achieving national health targets. The article further explores current challenges related to workforce distribution, competency development, and system integration, and highlights strategic priorities required to sustain reform momentum and optimise health outcomes.